Crowdsourcing Modern and Historical Data Identifies Sperm Whale (Physeter macrocephalus) Habitat Offshore of South-Western Australia - Johnson, Christopher M.; Beckley, Lynnath E.; Kobryn, Halina; Johnson, Genevieve E.; Kerr, Iain; Payne, Roger (Frontiers in Marine Science, 2016)
The distribution and use of pelagic habitat by sperm whales (Physeter macrocephalus) is poorly understood in the south-eastern Indian Ocean off Western Australia. However, a variety of data are available via online portals where records of historical expeditions, commercial whaling operations, and modern scientific research voyages can now be accessed. Crowdsourcing these online data allows collation of presence-only information of animals and provides a valuable tool to help augment areas of low research effort. Four data sources were examined, the primary one being the Voyage of the Odyssey expedition, a five-year global study of sperm whales and ocean pollution. From December 2001-May 2002, acoustic surveys were conducted along 5,200 nautical miles of transects off Western Australia including the Perth Canyon and historical whaling grounds off Albany; 60 tissue biopsy samples were also collected. To augment areas not surveyed by the RV Odyssey, historical Yankee whaling data (1712-1920), commercial whaling data (1904-1999), and citizen science reports of sperm whale sightings (1990-2003) were used. Using Maxent, a species distribution modeling tool, we found that the submarine canyons off Albany and Perth provide important habitat for sperm whales. Current technology, along with current understanding of sperm whale bioacoustics and habitat preferences, provides strong motivation for undertaking long-term passive acoustic studies that can monitor the sperm whale population within Australia’s EEZ waters (Perth and Albany canyons) as a way of informing future marine management and policy decisions.